How to touch what - Sonneman, Eve 1946-; Weiner, Lawrence 1942-2021 (PowerHouse Books, 2000)
Conceptual artist Lawrence Weiner and photographer Eve Sonneman have jointly produced a marriage of text and pictures that will keep the reader thinking, laughing and reading again and again.
Keywords: Sonneman, Eve; Weiner, Lawrence; Weiner, Lawrence -- 1942-2021; Sonneman, Eve -- 1946-; Artists' books -- United States; USA; Bildband